Two sides of the same coin? A new instrument to assess body checking and avoidance behaviors in eating disorders. (June 2017) - Legenbauer, Tanja; Martin, Franziska; Blaschke, Ariane; Schwenzfeier, Anne; Blechert, Jens; Schnicker, Katja
Highlights: New valid assessment instrument for body-related checking and avoidance behavior. Reassurance seeking is a third dimension of behavioral body image disturbance. Body-related avoidance behavior is present in all eating disorder categories. Body checking is strongest for women with anorexia and bulimia nervosa. In particular, body avoidance characterizes the presence of binge eating disorder. Abstract: Body checking (BC) and avoidance behaviors (BA) are the dominant behavioral features of body image disturbances (BID) that characterize most individuals with eating disorders (EDs). Whereas BC can be reliably assessed, a valid assessment tool for BA is lacking, preventing an adequate assessment of BID differences across different EDs (anorexia nervosa, AN; bulimia nervosa, BN; binge eating disorder, BED). A total of 310 women with EDs and 112 nonclinical controls completed measures of BC-, BA- and ED-related symptoms. BA did not differentiate between EDs, whereas BC did: it was highest in AN and BN, and lowest in BED. Multivariate analyses also discriminated AN from BN based on BC. Given that results are of preliminary nature, evidence is promising that EDs can be discriminated from healthy controls and that differential BID profiles for the behavioral component among ED subgroups exist. However, replication of the factor structure remains open within ED subsamples.